Building structure for double storey terrace house / Mohamad Razien Faiz Abdul Halim - Abdul Halim, Mohamad Razien Faiz (Universiti Teknologi MARA, Perak, 2015)
Superstructure is the most important element in building. Their role in making the building stable that safe for people to use. Therefore these reports will discuss and explain on how to construct a superstructure. The objective of this report is to shows on construction of superstructure and how to build it. This report will show he method of construction from pile cap to the roof beam of a double-storey terrace house at Taman Pasir Putih. This report also will show on what to do before and during the construction of the superstructure.